2016
DOI: 10.3389/fendo.2016.00126
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Venous Compliance in Young Women with Type 1 Diabetes – Further Aggravated by Prolonged Elevated Levels of HbA1c

Abstract: BackgroundYoung patients with diabetes present with reduced compensatory responses to hypovolemic stress. Less compliant veins could be a contributing factor, since roughly two-thirds of the blood volume resides in the venous system as a blood reservoir, adjusting proper venous inflow to the heart. The aim of this study was to measure venous compliance and lower limb blood pooling during hypovolemic stress, and to correlate them to indices of diabetes severity and glucose control.MethodsFifteen young women wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…2AeC). As previously mentioned, impaired venous compliance has been linked to hypertension and diabetes mellitus, 14,38 while reduced arterial compliance has been connected to smoking, 39 COPD, 40 and hyperlipidaemia. 41 The present study demonstrated that these risk factors were more common in patients with AAA.…”
Section: Venous Compliancementioning
confidence: 94%
See 1 more Smart Citation
“…2AeC). As previously mentioned, impaired venous compliance has been linked to hypertension and diabetes mellitus, 14,38 while reduced arterial compliance has been connected to smoking, 39 COPD, 40 and hyperlipidaemia. 41 The present study demonstrated that these risk factors were more common in patients with AAA.…”
Section: Venous Compliancementioning
confidence: 94%
“…To account for this, factors known to be associated with changes in venous or arterial compliance (hypertension, diabetes mellitus, smoking, COPD, and hyperlipidaemia) were adjusted for. 14,38,39,41 Secondly, no in vitro investigations were conducted and, as such, the histological components of elastin and collagen could not be evaluated. However, the aim of the present study was to assess haemodynamically important whole limb venous function.…”
Section: Limitationsmentioning
confidence: 99%
“…Venous capacitance, the ability of the vessel to accommodate changes in volume with minimal changes in pressure, is reduced in HF, obesity, diabetes, and inflammatory states, leading to increased central blood volume when stressed. [241][242][243] The volume loading of the central vascular compartment results in pulmonary and hemodynamic congestion, driving factors in development of PH and pulmonary vascular remodeling. Reduced PA capacitance in PH-LHD, which signals a lack of ability of the pulmonary vasculature to accommodate changes in volume loading, is associated with adverse outcomes.…”
Section: Splanchnic Circulationmentioning
confidence: 99%
“…The systemic veins (particularly the splanchnic venous system) normally act as a capacious reservoir, but changes in splanchnic venous tone can result in striking increases in central blood volume under physiological conditions (in response to acute hypovolaemia) or under pathological conditions (if systemic venous capacitance is impaired). Interestingly, inflammatory states (as well as both obesity and diabetes) are characterized by an impairment in systemic venous capacitance . Additionally, inflammatory‐metabolic HFpEF is a disease of elderly women, and both age and gender can further impair systemic venous function .…”
Section: Why Is the Left Ventricle Overfilled In Inflammatory‐metabolmentioning
confidence: 99%
“…Second, central blood volume may be increased in inflammatorymetabolic HFpEF because a decrease in systemic venous capacitance causes a redistribution of total blood volume from the periphery to the central compartment an impairment in systemic venous capacitance. 13,14 Additionally, inflammatory-metabolic HFpEF is a disease of elderly women, and both age and gender can further impair systemic venous function. 15 Abnormalities of systemic venous capacitance may become particularly marked during exercise and contribute to effort-induced increases in LV filling pressures.…”
Section: Mechanistic Distinction Among Phenotypes Of Heart Failure Wimentioning
confidence: 99%